Weak keys of the full MISTY1 block cipher for related‐key amplified boomerang cryptanalysis. (1st September 2018) - Lu, Jiqiang; Yap, Wun‐She; Wei, Yongzhuang
Abstract : The MISTY1 block cipher has a 64‐bit block size, a 128‐bit master key, and a total of 8 rounds. It is an ISO international standard, a Japanese CRYPTREC‐recommended e‐government cipher, and a European NESSIE selected cipher. In this study, the authors show another cryptographic weakness of the full MISTY1 cipher: they describe four classes of 2 90 weak keys of the full MISTY1 cipher for a related‐key amplified boomerang attack that has a data complexity of 2 60.5 chosen plaintexts and a time complexity of 2 87.33 encryptions under each class of weak keys. The result shows that the MISTY1 cipher can be distinguishable from an ideal cipher in terms of related‐key amplified boomerang cryptanalysis, and users should be very careful when using MISTY1 for a full security in relevant application situations.